Antithrombotic potential of Berberis calliobotrys extract (Bangladesh Journal of Pharmacology, 2016)
This study was focused with the aim to investigate the antithrombotic potential of Berberis calliobotrys. Aqueous-methanolic extract and various fractions showed significant (p